ANALYSIS OF DETERMINANT FACTORS IN IMPLEMENTING KNOWLEDGE MANAGEMENT AT PT PELINDO MULTI TERMINAL - Retno Lestari; Iskandarini; Prihatin Lumbanraja (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
The development of the logistics world, especially in ports, requires companies to continue to innovate for easier coordination nationally. Pelindo merged and divided the companies into subholdings. PT Pelindo Multi Terminal is one of the subholdings of Pelindo that carries out loading and unloading of non-container cargo. Post-merger, the fusion of culture and technology systems used for company operations and company knowledge management has undergone many changes. This study aims to determine the effect of Organizational Culture, Personal Knowledge, Job Procedure, and Technology on Knowledge Management at PT Pelindo Multi Terminal. This type of research is associative. The population in this study were all active workers of PT Pelindo Multi Terminal with samples obtained from the purposive sampling method totaling 247 workers. The data analysis used was multiple linear regression analysis. The results of this study indicate that simultaneously organizational culture, Personal Knowledge, Job Procedure, and Technology have a positive and significant effect on the implementation of Knowledge Management at PT Pelindo Multi Terminal. Partially, organizational culture, Personal Knowledge, Job Procedure, and Technology have a positive and significant effect on the implementation of Knowledge Management at PT Pelindo Multi Terminal.